The application of microwave preheating in resin transfer moulding - Johnson, Michael S. (1995)
Fibre reinforced plastics (FRP) are of considerable interest to the automotive industry. Intelligent application of these materials could reduce vehicle weight for higher operating efficiency, at a reduced manufacturing cost. The principal use of FRP in high volume (greater than 100,000 parts per annum) has been restricted to non-structural body panels made from short fibre reinforcement. Long fibre reinforced composites are ideal for load bearing structures resulting from a high specific strength. However, a high volume technique to produce these components at a moderate cost has not been realised. One long fibre reinforcement process with the potential to meet the high volume demands of the automotive industry is resin transfer moulding (RTM).